Golf: Duo strike gold - Malay, Mail (Malay Mail, 2015)
Shah Alam - Selangor and national golfer Galven Kendall Green retained the DRB-Hicom Tan Sri Muhyiddin (TSM) Golf Challenge for the second successive year.